STRATEGY FOR THE IMPLEMENTATION OF QUALITY MANAGEMENT POLICY ON TUNA FISHERIES IN SENDANG BIRU MALANG - Furqan, Imam; Nurani, Tri Wiji; Solihin, Iin (Universitas Brawijaya, Indonesia, 2017)
Concern the government of the importance of the quality of fishery products as set out in KEPMEN-KP/52A/2013 should be followed up through the implementation of quality systems in fisheries activities. The purpose of this research was formulating development strategies and steps for the successful implementation of quality management in tuna fisheries in Sendangbiru. The analysis methods that used in this research is balanced scorecard. The result show, strategic target of implementation quality management policies on tuna fisheries in Sendangbiru are the quality of tuna produced A and B, equipment and facilities complete, distribution vehicles viable, use of technology, and availability counseling and supervision of the activities of tuna handling.